2012
DOI: 10.1007/s10681-012-0704-2
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Bemisia tabaci in tomato wild relatives

Abstract: Bemisia tabaci is one of the most threatening pests in agriculture, particularly in Solanaceous crops such as tomato and pepper that are cultivated in the open field. Pesticide application is often not effective and hazardous to humans and environment. The exploitation of plant natural defenses that are present in wild relatives of tomato, may offer a solution. To evaluate resistance parameters and to identify plant material with high levels of resistance, we screened a number of accessions of tomato wild rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
88
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 56 publications
(83 reference statements)
10
88
0
4
Order By: Relevance
“…Hybrids produced using this species supported the fewest eggs and were the least attractive hosts of the whitefly. Firdaus et al (2012) also considered oviposition and found one accession of L. pimpinellifolium to be resistant on the basis of supporting low levels of egg-laying, as corroborated by the present work.…”
Section: No Choice Assays To Record Whitefly Ovipositionsupporting
confidence: 85%
See 3 more Smart Citations
“…Hybrids produced using this species supported the fewest eggs and were the least attractive hosts of the whitefly. Firdaus et al (2012) also considered oviposition and found one accession of L. pimpinellifolium to be resistant on the basis of supporting low levels of egg-laying, as corroborated by the present work.…”
Section: No Choice Assays To Record Whitefly Ovipositionsupporting
confidence: 85%
“…However, as statistical output matched that from the other four runs (where this assumption was not violated), results of run 1 were retained and included herein. Firdaus et al (2012) examined a range of wild tomato relatives for resistance to B. tabaci. They found that L. pimpinellifolium showed little evidence of being less preferable to B. tabaci based upon free choice assays, which is in contrast to the findings presented here.…”
Section: Free Choice Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, spontaneous field-exposure infection has been shown to be largely inefficient, as many plants escape infection, even under heavy inoculation pressure (Vidaysky et al, 1998). To identify plant materials having high level of resistance, screening of genotypes using force feeding methods (Firdaus et al, 2012;Taggar et al, 2013;Sulistyo and Inayati, 2016)and agroinoculation methods (Al Abdallat et al, 2010;Karthikeyan et al, 2011;B Sai et al, 2017) has been exploited in several crops including mungbean. Therefore, it is essential to screen genotypes through forced feeding methods, which can ensure 100% infection rate, and a standardized inoculum pressure.…”
Section: Issn: 2319-7706 Volume 7 Number 04 (2018)mentioning
confidence: 99%